Pengenalan Literasi Baca Tulis Pada Bahan Bacaan Sains Pada Siswa Paud Rafa Kota Bengkulu - Fitria, Yenni; Imran , Ranny Fitria; Ariyanti , Tri Dina; Lestari , Titje Puji; Oktafiyani, Winda; Sari, Minti Okta; Eleza , Wellen (Universitas Dehasen Bengkulu, 2020)
Digital literacy creates a social order with a critical-creative mindset and outlook. They will not be easily influenced by provocative issues, so they will become victims of digital-based hoaxes or fraud. Thus, the social and cultural life of the community will tend to be safe and conducive. Building a digital literacy culture needs to involve the active role of the community together. In simple terms, literacy is defined as an activity that involves reading and writing. Introduction to Digital Literacy for PKBM Participants in the City of Bengkulu, departing from the problems faced by the PKBM in the City of Bengkulu regarding how to teach material through digital literacy in learning Indonesian. The purpose of this socialization is to raise the enthusiasm of students at PKBM Bunda Sciences in the City of Bengkulu in participating in learning Indonesian with digital literacy. Implementation of Community Service activities by collaborating between lecturers at Dehasen Bengkulu University and PKBM in the City of Bengkulu by providing socialization on the introduction of digital literacy as an initial step to see the responses of PKBM in the Bengkulu City of Mother Science in the learning process and applying it directly in the digital world so that more interesting learning. Basically, learning activities are based on reading and writing activities. In this training, reading and writing techniques can be delivered to improve students' abilities to explore themselves using digital media. The use of digital tools or media makes it easier for students to learn because they keep up with the times. Students who are diligent in writing can write on blogs and blogs that are read by many people so that the reading material we create will be useful for others.